ASSESSMENT OF CARBON EMISSIONS FROM THE WASTE MANAGEMENT SECTOR IN AJATAPPARENG REGION, SOUTH SULAWESI, INDONESIA - Irwan Ridwan Rahim; Kartika Sari; Muhammad Ihsan Mukrim Mukrim; Alfiyah Zhafirah Iman; Achara Taweesan; Zin Aung Swe (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2025)
Ajatappareng is a region in South Sulawesi Province, Indonesia which consists of four regencies and one administrative city. The regencies are Barru, Sidenreng Rappang, Pinrang, and Enrekang while the city is Parepare. The area has experienced a significant growth in terms of population which further leads to an increase in waste generation. Waste are a major challenge for environmental management especially due to the role in producing carbon emissions.  Aim: This study aims to assess the carbon emissions produced in waste management sector of the Ajatappareng Region. Methodology and results: The GHG Simulation-Version II spreadsheet was used to assess the GHG emissions from the transportation of waste in the respective regencies. Mathematical formulas were provided in the cells to calculate the GHG emissions of the simulation developed. Conclusion, significance, and impact study: The results showed that the volume of carbon emissions was 16,299.84 kg CO2-eq/month for Barru Regency, 17,076.03 kg CO2-eq/month for Sidrap Regency, 16,817.30 kg CO2-eq/month for Parepare City, 17,722.85 kg CO2-eq/month for Pinrang Regency, and 19,145.85 kg CO2-eq/month for Enrekang Regency. Moreover, the GHG emissions from mixed waste in the final disposal site were 918,531.01 kg CO2-eq/month, 1,733,537.85 kg CO2-eq/month, 1,404,917.59 kg CO2-eq/month, 1,723,004.12 kg CO2-eq/month, and 523,506.36 kg CO2-eq/month, respectively. Therefore, potential efforts are required to reduce CO2 emissions by optimizing waste transportation, promoting recycling, managing organic waste through composting, as well as improving collaborations with the private sector.